2019
DOI: 10.1585/pfr.14.2402023
|View full text |Cite
|
Sign up to set email alerts
|

First Experimental Campaign on SMOLA Helical Mirror

Abstract: Experimental evidence of the plasma flow suppression by the helical magnetic mirror is presented. Reported experiments were done during the first plasma campaign in the SMOLA helical mirror device at self-consistent floating potentials of all in-vessel electrodes and at minimal magnetic fields suitable for confinement regime. The experimental results are consistent with two main theory predictions for the helical mirror confinement: a reduction of the axial plasma flow and the inward particle pinch. The helica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…In the experiment, plasma stream produced by a plasma gun was passed through a helical multi-mirror section. It was observed that plasma flow at the end of the section was significantly decreased in agreement with the theoretical prediction [23] independently from the plasma collisionality varied in the broad range [24]. This result is rather promising for the application of such an end section in the GDT-based neutron source for the reduction of plasma end losses.…”
Section: Simulations and Experimentssupporting
confidence: 76%
“…In the experiment, plasma stream produced by a plasma gun was passed through a helical multi-mirror section. It was observed that plasma flow at the end of the section was significantly decreased in agreement with the theoretical prediction [23] independently from the plasma collisionality varied in the broad range [24]. This result is rather promising for the application of such an end section in the GDT-based neutron source for the reduction of plasma end losses.…”
Section: Simulations and Experimentssupporting
confidence: 76%
“…Concept exploration of the helical mirror SMOLA was put into operation at Budker Institute of Nuclear Physics at the end of 2017 (Postupaev et al 2016;Sudnikov et al 2017). Axial plasma flux suppression by the helical sections was demonstrated in the first experimental campaign, an integral suppression ratio of 2-2.5 was achieved (Sudnikov et al 2019). An improvement of the suppression ratio with the increase of the magnetic field, corrugation ratio and plasma rotation velocity was demonstrated (Sudnikov et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the axial plasma flow suppression was already demonstrated in the first experiments (Sudnikov et al . 2019) with an incomplete configuration of subsystems of the device.…”
Section: Introductionmentioning
confidence: 99%